Economic indicators in the implantation of eucalyptus citriodora – Corymbia citriodora (Hook.) K.D. Hill & L.A.S. Johnson cultivation - Furtado, Jhécika da Silva; Garcia, Bianca; da Silva, Andrécia Cósmem; da Silva, Danilo; Araújo, Matheus da Silva; Henrique, Gabriel (Science & Technology Journals, 2020)
This study aimed to build economic indicators on the implementation of eucalyptus in the state of Goiás. For this purpose, indicators such as net present value (NPV), benefit/cost ratio (BC), sensitivity analysis and application of the economic payback of invested capital were calculated and discussed. In order to evaluate the effect of crop viability in the face of unexpected situations, impacts on the crop were also estimated in four scenarios involving the project. The results indicated that for the discount rate of 6.5% p.a., NPV was R 14,298.93 for one hectare, showing that the investment is viable. The BC ratio was greater than 1 (BC > 1), demonstrating that the benefits of the implementation outweighed the costs, and the period of time that will be elapsed until the return on the initial investment has shown that the return for 1 ha and 6 ha will take place in the seventh year. Likewise, it was found that for all the estimated scenarios there was economic viability for the implementation of the crop.